2020
DOI: 10.3393/ac.2020.02.28
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience With Video-Assisted Anal Fistula Treatment in the Philippines

Abstract: Purpose: We determined the outcomes of patients undergoing video-assisted anal fistula treatment (VAAFT) for fistulain-ano at the Philippine General Hospital.Methods: Twenty consecutive adult patients who underwent the VAAFT procedure from 2016–2018 were included in this investigation. Information detailing baseline demographic and clinical data, fistula type and classification, and previous surgeries were retrieved from in-hospital and operative records. Operative time, identification of the internal opening,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(32 reference statements)
0
3
1
1
Order By: Relevance
“…In our study, the rate of primary healing was lower than that seen in the two VAAFT meta‐analyses performed to date (covering 12 individual studies) which reported pooled rates of healing of 82.3% at 9 months median follow up 19 and 76% at 7 months follow up 22 . Studies performed since these reviews have demonstrated primary healing rates ranging from 54% to 81% at follow up ranging from 6 to 36 months 23–28 . The lower rate of primary healing witnessed in our study is perhaps explained by the complexity of included disease, but also the longer duration of follow up (mean 59.5 months).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In our study, the rate of primary healing was lower than that seen in the two VAAFT meta‐analyses performed to date (covering 12 individual studies) which reported pooled rates of healing of 82.3% at 9 months median follow up 19 and 76% at 7 months follow up 22 . Studies performed since these reviews have demonstrated primary healing rates ranging from 54% to 81% at follow up ranging from 6 to 36 months 23–28 . The lower rate of primary healing witnessed in our study is perhaps explained by the complexity of included disease, but also the longer duration of follow up (mean 59.5 months).…”
Section: Discussioncontrasting
confidence: 68%
“…22 Studies performed since these reviews have demonstrated primary healing rates ranging from 54% to 81% at follow up ranging from 6 to 36 months. [23][24][25][26][27][28] The lower rate of primary healing witnessed in our study is perhaps explained by the complexity of included disease, but also the longer duration of follow up (mean 59.5 months). The latter is an important consideration as the rate of recurrence of FIA is known to increase out to 5 years post intervention.…”
Section: Discussionmentioning
confidence: 60%
“…VAAFT is an emerging treatment method that brings hope to the treatment of anal fistula (26). It is still unclear whether video assistance is critical to the success of the surgery; some supporters believe that even the lesions missed by MRI can be found using VAAFT.…”
Section: Discussionmentioning
confidence: 99%
“…У одного пациента зарегистрирован рецидив свища. У одного пациента во время контрольного осмотра через 6 месяцев установлена инконтиненция с недержанием газов и стула [11].…”
Section: результаты и обсуждениеunclassified